2009
DOI: 10.1371/journal.pone.0006331
|View full text |Cite
|
Sign up to set email alerts
|

Human Protein Phosphatase PP6 Regulatory Subunits Provide Sit4-Dependent and Rapamycin–Sensitive Sap Function in Saccharomyces cerevisiae

Abstract: In the budding yeast Saccharomyces cerevisiae the protein phosphatase Sit4 and four associated proteins (Sap4, Sap155, Sap185, and Sap190) mediate G1 to S cell cycle progression and a number of signaling events controlled by the target of rapamycin TOR signaling cascade. Sit4 and the Sap proteins are ubiquitously conserved and their human orthologs, PP6 and three PP6R proteins, share significant sequence identity with their yeast counterparts. However, relatively little is known about the functions of the PP6 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 41 publications
0
17
0
1
Order By: Relevance
“…9). Indeed, in budding yeast, the regulatory subunits SAP1, SAP2, and SAP3 have each been shown to confer different properties on Sit4, the yeast homologue of PP6c (41). We speculate that one possible function of the different PP6 complexes may be to target ␥-H2AX at foci that are located at different distances from the DSB site.…”
Section: Discussionmentioning
confidence: 91%
“…9). Indeed, in budding yeast, the regulatory subunits SAP1, SAP2, and SAP3 have each been shown to confer different properties on Sit4, the yeast homologue of PP6c (41). We speculate that one possible function of the different PP6 complexes may be to target ␥-H2AX at foci that are located at different distances from the DSB site.…”
Section: Discussionmentioning
confidence: 91%
“…PP6 is conserved among all eukaryotic species from yeast to humans, attesting to its fundamental importance. The Saccharomyces cerevisiae homologue, Sit4, is required for G 1 to S progression, expression of G 1 cyclins, and several other cellular processes (23,26). The human PP6 also promotes G 1 to S progression, predominantly by regulating the levels of cyclin D1 (27).…”
mentioning
confidence: 99%
“…In fact, R1, R2 and R3 were originally identified by the sequence homology of their SAPS domains to their yeast counterparts (31). Although the different PP6c regulatory subunits may have some redundant functions, as in the case of Aurora A dephosphorylation (28), there is evidence that each subunit may also have specific non-redundant functions (26,31). Knockdown of R1, but not R3, enhances degradation of endogenous IB⑀ in response to TNF-␣ (31).…”
mentioning
confidence: 99%
“…It has further been reported that human SAPS, when expressed in S. cerevisiae , are able to physically interact with Sit4, and that the expression of either SAPS2 or SAPS3, but not SAPS1, can rescue the growth defect and rapamycin sensitivity of yeast cells lacking all four yeast SAPs. This effect was dependent on the presence of Sit4 [12]. …”
Section: Introductionmentioning
confidence: 99%